Arabis Recta Vill. (Brassicaceae) In Poland: Distribution, Habitats And Threat Assessment - Nobis, Marcin; Nobis, Agnieszka (Biodiversity: Research and Conservation, 2012)
Arabis recta is one of the rarest species in Poland. It has been reported from 15 sites, mostly in the Nida Basin (Ma≥opolska Upland). The plant is a component of xerothermic grasslands but it can also grow in arable fields and fallows. In Poland, Arabis recta is considered to be threatened by natural succession and herbicide use. However, according to recent studies, it should be treated as an endangered species (EN category) in the country.